1613. Global 2018 Surveillance of Eravacycline Against Gram-negative Pathogens, Including Multi-drug Resistant Isolates. (31st December 2020) - Lijfrock, Virgil; Morgan, Steven; Hwang, Sara; Efimova, Ekaterina; Lawrence, Kenneth; Hawser, Stephen; Morrissey, Ian
Abstract: Background: Eravacycline (ERV) is a fully-synthetic, fluorocycline antibacterial approved by the FDA and EMA for treatment of complicated intra-abdominal infections (cIAI) in patients ≥18 years of age. The purpose of this study was to describe the in vitro activity of ERV against Gram-negative pathogens, including multi-drug resistant (MDR) isolates, collected in 2018. Methods: Isolates were collected during 2018 from various body sites. Minimum inhibitory concentrations (MICs) were determined by CLSI broth microdilution. Antibiotic susceptibility was determined using the most updated CLSI breakpoints, except for ERV and tigecycline (TGC) where FDA breakpoints established in 2018 and 2005 respectively, were used. MDR was defined as resistance to ≥3 antibiotics from aztreonam, a carbapenem (meropenem or ertapenem [ETP]), cefepime/cefotaxime/ceftazidime/ceftriaxone (any one), gentamicin, levofloxacin, piperacillin-tazobactam TZP, tetracycline or TGC. Results: Summary MIC data for ERV and select comparators are shown in the Table. ERV MIC90 for all-Enterobacteriaceae was 0.5 μg/ml and for MDR-Enterobacteriaceae was 1μg/ml. The susceptibilities for all-Enterobacteriaceae were 93%, 95%, 93% and 82% for ERV, TGC, ETP and TZP, respectively. ERV further demonstrated higher rates of susceptibility than ETP and TZP against MDR-Enterobateriaceae, 81% vs 71% vs 38%. ERV MIC50/90 for carbapenem-resistant Acinetobacter baumannii (CRAB) were 4-fold lower than TGC. Table Conclusion: ERV in vitro activity was demonstrated and comparable susceptibility rates were observed for clinically important Gram-negative pathogens, including resistant isolates. Overall, ERV MIC90 values were 2- to 8- fold lower than TGC. this study further highlights the in vitro activity of ERV against Gram-negative pathogens identified in patients with cIAI. Disclosures: Virgil Lijfrock, PharMD, Tetraphase (Employee) Steven Morgan, PharMD, Tetraphase Pharmaceuticals (Employee) Sara Hwang, PharMD, Tetraphase Pharmaceuticals (Employee) Ekaterina Efimova, PharMD, Tetraphase Pharmaceuticals (Employee) Kenneth Lawrence, PharmD, Tetraphase Pharmaceuticals (Employee) Stephen Hawser, PhD, Tetraphase Pharmaceuticals (Scientific Research Study Investigator) Ian Morrissey, PhD, Tetraphase Pharmaceuticals (Scientific Research Study Investigator)